Photocatalytic Decolourization of Reactive Dyes Using Silver Incorporated Titania Catalyst. (2016) - Vaithiyanathan, R.
Abstract: Photocatalytic decolourization of four different commercial textile azo dyes was studied under UV irradiation (365 nm) using titania catalysts, synthesized via sol gel method. In order to improve the photocatalytic activity of bare TiO2, silver metal impregnated titania catalysts containing varying amount of silver metal from 0.5-2.0% were synthesized and their photocatalytic activities towards the decolourization of selected dyes was studied. Result revealed that all the silver metal modified catalysts were found to have a superior photocatalytic activity than bare TiO2 and also it was observed that at higher loading of silver metal (beyond 1%), photocatalytic activity of titania was suppressed. Among the catalysts, 1% Ag impregnated titania was found to be the best one in the decolourization of all the dye solutions which may be due its lower band gap value (3.07 eV) and effective separation of electron-hole recombination by silver metal. All the synthesized photocatalysts were characterized by XRD and DRS techniques.